DIVERSITY AND DENSITY OF VECTOR FOR LYMPHATIC FILARIASIS IN BUTON DISTRICT, SOUTH EAST SULAWESI PROVINCE, INDONESIA - Wigati, RA; Andiarsa, Dicky; Setyaningtyas, Dian Eka (Berita Biologi, 2025)
A study was conducted in Buton District, Southeast Sulawesi, to ascertain the diversity and density of mosquito species and to determine the potential for transmission, prevention, and control of filariasis. The findings of this study serve as a baseline for the assessment and monitoring of the risk of filariasis disease, which may contribute to the prevention of future transmission. The collection methods employed involved the use of landing collection techniques, with several modifications to standard procedures. The identification of mosquitoes was conducted using a dissecting microscope and a mosquito identification key book. The collection yielded a total of 1,100 mosquitoes, classified into seven genera: Aedes, Anopheles, Armigeres, Coquilettidia, Culex, Mansonia, and Uranotaenia. The composition of the collection included 1,035 Culex, 27 Armigeres, 22 Anopheles, 11 Aedes, 2 Mansonia, 2 Uranotaenia, and 1 Coquilettidia. These numbers represented 94.09%, 2.45%, 2.00%, 1.00%, 0.18%, 0.18%, and 0.09%, respectively. The 23 distinct species of mosquito identified based on their morphological characteristics included nine species of Culex, six species of Anopheles, three species of Aedes, two species of Armigeres, and one species belonging to Coquilettidia, Mansonia, and Uranotaenia. Of particular note are the two species, Cx. quinquefasciatus and Cx. vishnui, which exhibited a high density. These species were found to be dominant in both outdoor and indoor human dwellings. Notably, Cx. quinquefasciatus and Cx. vishnui have been identified as potential risk factors for filariasis transmission, highlighting the need for continued surveillance and monitoring in filariasis-endemic regions.